2014
DOI: 10.1517/13543784.2014.873785
|View full text |Cite
|
Sign up to set email alerts
|

Discontinued drug projects in the respiratory therapeutic area during 2012

Abstract: During 2012, a number of respiratory drug projects and individual agents were discontinued, for a variety of reasons, including toxicity, lack of efficacy, commercial re-evaluation and change in corporate focus. These included three antagonists of chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTh2), which had been evaluated in allergic respiratory disease and (in one case) chronic obstructive pulmonary disease (COPD), and other agents intended for the treatment of asthma, COPD, pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 3 , 13 , 27 29 A number of inhibitors of CRTH2 have already been tested in the treatment of various disease states. Although some studies reported that inhibition of CRTH2 was unsuccessful in ameliorating symptoms of COPD or asthma and allergic rhinitis in patients, 31 , 37 , 38 other clinical trials targeting CRTH2 have shown promising efficacy data in the treatment of asthma and allergic rhinitis. 28 , 39 , 40 Notably, our results showed that chemical inhibition of CRTH2 ameliorated some, but not all, effects of helminth infection in the lung, as OC000459 treatment did not appear to decrease helminth-induced pulmonary goblet cell hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 13 , 27 29 A number of inhibitors of CRTH2 have already been tested in the treatment of various disease states. Although some studies reported that inhibition of CRTH2 was unsuccessful in ameliorating symptoms of COPD or asthma and allergic rhinitis in patients, 31 , 37 , 38 other clinical trials targeting CRTH2 have shown promising efficacy data in the treatment of asthma and allergic rhinitis. 28 , 39 , 40 Notably, our results showed that chemical inhibition of CRTH2 ameliorated some, but not all, effects of helminth infection in the lung, as OC000459 treatment did not appear to decrease helminth-induced pulmonary goblet cell hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that generation of mucus metaplasia involves a complex interplay among IL-25, IL-33 and TSLP. Nevertheless, blocking the TSLP pathway alone appears sufficient to suppress inflammation, as shown so far in the tezepelumab studies, albeit other anti-TSLP biologics such as RG7258 were not successfully developed into asthma therapies [108]. To date, no clinical studies have investigated the potential interactions between alarmins in patients with asthma, but it would be of importance to understand such interactions, both in terms of effects on the efficacy and safety of these treatments.…”
Section: Outstanding Questions Regarding Anti-alarminsmentioning
confidence: 99%
“…78,114 However, AZX100 was later not pursued owing to financial reasons. 115 The safety and tolerability of the cationic carriers as demonstrated in these clinical trials emphasizes that using cationic carriers for drug delivery applications is practical if the dosing needed to induce an effective biological response remains below the cytotoxic concentration of the carrier.…”
Section: Clinical Translationmentioning
confidence: 99%